Stakeholder perspectives of the sociotechnical requirements of a telehealth wheelchair assessment service in Aotearoa/New Zealand: A qualitative analysis. (22nd January 2022) - Graham, Fiona; Boland, Pauline; Jones, Bernadette; Wallace, Sally; Taylor, William; Desha, Laura; Maggo, Jasjot; McKerchar, Christina; Grainger, Rebecca
Abstract: Introduction: Telehealth is widely proposed to improve access and equity in provision of rehabilitation, including wheelchair assessment, yet the design requirements of telehealth wheelchair assessment that will be accepted and utilised at scale are unclear. Service design that addresses the existing inequities in outcomes for indigenous populations, such as Māori will be critical. The aim of this study was to examine the design requirements of a telehealth wheelchair assessment service from the perspectives of key stakeholders such as wheelchair users and their families, including indigenous (Māori) and health professionals including occupational therapist, and physiotherapist assessors and technicians. Methods: Within a wider mixed methods design, inductive thematic analysis was applied to focus group and interview data from 23 assessors (19 occupational therapists and four physiotherapist assessors, one of whom was Māori) and 19 wheelchair users (three of whom were Māori). Results: Eight themes were discerned with the final three themes emphasising the experiences of particular concern to Māori: (1) At the mercy of the system ; (2) The hurdle of technology ; (3) More efficient for all ; (4) Lost information and connection ; (5) Rights and the right way forward ; (6) Cultural safety ; (7) Whanaungatanga (relationship building) ; and (8) Summative disadvantage for Tāngata whaikaha (Māori with disabilities) . Themes reflected a recognition of risks and uncertainty associated with tele‐delivered assessment. Conversely, advantages in access, equity, and professional competency were reimagined. Perspectives of Māori included both risks and advantages as perceived by Māori. Conclusion: Substantial dissatisfaction with current wheelchair assessment services among wheelchair users provides context to the impetus for a successful design of a telehealth assessment service. Training in conducting telehealth wheelchair assessment is essential incorporating culturally safe communication practices and support of wheelchair user autonomy while identifying solutions that achieve wheelchair user goals.